1990
DOI: 10.1128/aac.34.8.1467
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of antimicrobial agents against Toxoplasma gondii by quantification of parasites in the blood, lungs, and brain of infected mice

Abstract: The in vivo effects of antimicrobial agents against Toxoplasma gondii were evaluated in mice that were infected intraperitoneally with 104 tachyzoites of the RH strain by determination of survival rates and study of the kinetics of growth of T. gondi in infected mice. At various intervals after infection, subcultures of serial dilutions of blood, lung, and brain homogenates were performed in fibroblast tissue cultures for determination of parasitic loads. Pyrimethamine (18.5 mg/kg per day), sulfadiazine (375 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
2

Year Published

1992
1992
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 13 publications
6
38
2
Order By: Relevance
“…All the control mice died within 7 (range, 5 to 7) days. As in a previous study (11), parasite burdens were constantly higher in lung than in brain or blood; at day 4, the mean values of four experiments (20 mice) were 6.31 ± 0.7 log units in lung, 3.8 ± 0.4 in brain, and 2.3 ± 2 in blood.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…All the control mice died within 7 (range, 5 to 7) days. As in a previous study (11), parasite burdens were constantly higher in lung than in brain or blood; at day 4, the mean values of four experiments (20 mice) were 6.31 ± 0.7 log units in lung, 3.8 ± 0.4 in brain, and 2.3 ± 2 in blood.…”
Section: Resultssupporting
confidence: 51%
“…In contrast, parasites were not detectable in blood and were cleared from lungs. This specific efficacy was probably the main reason for the prolonged survival of treated mice, since pulmonary toxoplasmosis is the principal cause of death in this model of acute infection (11). This special effect on lung infection may be explained in part by the pharmacokinetics of azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Following 2 h of incubation at 37°C, the suspension was distributed into two six-well culture plates, diluted in PBS, and scanned by light microscopy (magnification, ϫ20) to count the blue-stained cysts. Determination of parasite burden in the organs was performed by a tissue culture method adapted from that of Piketty et al (25): (i) blood (200 l) of infected rats was collected from the retro-orbital sinus into Vacutainer Systems tubes (HEMOGARD SST; Becton Dickinson), diluted into 4 ml of PBSA (0.01 M PBS, pH 7.4, supplemented with 100 U/ml penicillin, 50 l/ml streptomycin, 0.04 l/ml gentamicin, and 2.5 g/ml amphotericin B), and (ii) the organs were removed, washed in PBSA, weighed, and homogenized, using a Potter homogenizer, into various volumes of PBSA (4 ml for the spleen and 2 ml for mesenteric lymphatic nodes). Serial fourfold dilution of homogenates were prepared in Dulbecco's modified Eagle's medium supplemented with antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, serial fourfold dilutions of each blood or organ suspension were prepared in the culture medium, and then 40 ,ul of each dilution was inoculated into duplicate wells of tissue culture plates. Previous experiments using the same experimental procedure had shown that antimicrobial agents in ground tissue had no effect on parasitic growth in the cultures (12). After the parasite burden for five mice (+ 1 standard error) was calculated for each time point.…”
mentioning
confidence: 99%
“…Monitoring of infection involved the estimation of survival rates by using the Kaplan Meier product limit method and sequential examination of parasite burden in blood, brains, and lungs on days 4, 7, 10, 14, 22, and 30 after infection; on day 30, liver and spleen tissues were also examined. At each time point, five mice from each group were sacrificed and blood and organ homogenates were cultured as described previously (12). Briefly, serial fourfold dilutions of each blood or organ suspension were prepared in the culture medium, and then 40 ,ul of each dilution was inoculated into duplicate wells of tissue culture plates.…”
mentioning
confidence: 99%